Pyrosequencing analysis of microbial community and food-borne bacteria on restaurant cutting boards collected in Seri Kembangan, Malaysia, and their correlation with grades of food premises - Abdul Mutalib, Noor Azira; Amin Nordin, Syafinaz; Osman, Malina; Ishida, Natsumi; Tashiroe, Kosuke; Sakaid, Kenji; Tashirod, Yukihiro; Maedaa, Toshinari; Shirai, Yoshihito (Elsevier BV, 2015)
This study adopts the pyrosequencing technique to identify bacteria present on 26 kitchen cutting boards collected from different grades of food premises around Seri Kembangan, a city in Malaysia. Pyrosequencing generated 452,401 of total reads of OTUs with an average of 1.4 × 107 bacterial cells/cm2. Proteobacteria, Firmicutes and Bacteroides were identified as the most abundant phyla in the samples. Taxonomic richness was generally high with > 1000 operational taxonomic units (OTUs) observed across all samples. The highest appearance frequencies (100%) were OTUs closely related to Enterobacter sp., Enterobacter aerogenes, Pseudomonas sp. and Pseudomonas putida. Several OTUs were identified most closely related to known food-borne pathogens, including Bacillus cereus, Cronobacter sakazaki, Cronobacter turisensis, Escherichia coli, E. coli O157:H7, Hafnia alvei, Kurthia gibsonii, Salmonella bongori, Salmonella enterica, Salmonella paratyphi, Salmonella tyhpi, Salmonella typhimurium and Yersinia enterocolitica ranging from 0.005% to 0.68% relative abundance. The condition and grade of the food premises on a three point cleanliness scale did not correlate with the bacterial abundance and type. Regardless of the status and grades, all food premises have the same likelihood to introduce food-borne bacteria from cutting boards to their foods and must always prioritize the correct food handling procedure in order to avoid unwanted outbreak of food-borne illnesses.